THE NATIONAL ONCOLOGICAL PROGRAM IMPLEMENTATION – EXPERIENCE IN THE VLADIMIR REGION (TO THE 70TH ANNIVERSARY OF THE REGIONAL CLINICAL ONCOLOGICAL DISPENSARY) - A. G. Zirin; E. A. Rumyantseva; K. V. Chirkov; M. N. Bulanov; G. V. Shatalova; Yu. L. Timofeev; A. V. Basharin; I. A. Konyukhov; A. V. Sheiko (Исследования и практика в медицине)
By 2010, on the background of the steady increase in the incidence of malignant tumors in the Vladimir area, primary oncological care level worked inefficiently.Condition of material and technical base of the Vladimir Regional Clinical Oncological Dispensary was also unsatisfactory. All these problems required solution in the form of the National Oncology Program realization in the region. The National Oncological Program has begun to work in the Vladimir region since 2011. Target indicators of the oncological program implementation by 2015 were established. They are: Increase of 5-year survival value of patients with malignant tumors after diagnosis date to 51.4%; Increase the number of malignant tumors early detection cases at the I–II stages up to 51%; Decrease the mortality rate of working age population to 99 per 100 000; Decrease of mortality within one year from the first time of cancer diagnosis to 27%. The following main objectives such as radically improved the material and technical base of oncology dispensary; modern methods of prevention, diagnosis and patients treatment improvement and introduction; the system providing population cancer care focused on the cancer early detection and the specialized combined antitumor treatment provision are realized in order to achieve these goals. The implementation of the tasks allowed to achieve positive dynamics of Vladimir region population cancer care indicators. All the main targets of the National Oncology Program for the Vladimir region were achieved successfully. Implementation of the National Oncology Program has had an extremely positive effect on the cancer services development of, as well as for the health of the entire population of the Vladimir region.